Recent Advances on Cell-Based Co-Culture Strategies for Prevascularization in Tissue Engineering - Shafiee, Sepehr; Shariatzadeh, Siavash; Zafari, Ali; Majd, Alireza; Niknejad, Hassan (Frontiers in Bioengineering and Biotechnology, 2021)
Currently, the fabrication of a functional vascular network to maintain the viability of engineered tissues is a major bottleneck in the way of developing a more advanced engineered construct. Inspired by vasculogenesis during the embryonic period, the in-vitro pre-vascularization strategies have focused on optimizing communications and interactions of cells, biomaterial and culture conditions to develop a capillary-like network to tackle the aforementioned issue. Many of these studies employ a combination of endothelial lineage cells and supporting cells such as mesenchymal stem cells, fibroblasts, and perivascular cells to create a lumenized endothelial network. These supporting cells are necessary for the stabilization of the newly developed endothelial network. Moreover, to optimize endothelial network development without impairing biomechanical properties of scaffolds or differentiation of target tissue cells, several other factors, including target tissue, endothelial cell origins, the choice of supporting cell, culture condition, incorporated proangiogenic factors, and choice of biomaterial must be taken into account. The prevascularization method can also influence the endothelial lineage cell/supporting cell co-culture system to vascularize the bioengineered constructs. This review aims to investigate the recent advances on standard cells used in in vitro pre-vascularization methods, their co-culture systems, and conditions in which they form an organized and functional vascular network.